RELIGIOUS TOURISM: AN ANALYSIS OF ANTECEDENTS OF THE INTENTION TO PARTICIPATE IN RELIGIOUS FESTIVALS - Govender, Kelisha; Chiliya, Norman; Chuchu, Tinashe; Maziriri, Eugine Tafadzwa; Ndoro, Tinashe (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2020)
Religious tourism relates to tourism which is motivated by faith or religious beliefs. Religious tourism has resulted in individuals moving from one place to the other for purposes of partaking in religious festival celebrations. The purpose of the present study was, therefore, to investigate the antecedents of intention to engage in religious festivals. To provide context to the research, two religious festivals were the focus of the study namely, Holi and Christmas. Non-probability sampling, a form of convenience sampling, was adopted in selecting participants. Data was obtained from 224 participants who reside in Johannesburg, South Africa. Data collection involved the administration of a survey questionnaire. The antecedents of the intention to participate in religious festivals included attitudes and subjective norms. The findings from the study suggested that attitudes had the most significant impact on intention to engage in religious festivals. Suggestions for future research and implications of the research are discussed.